THE EFFECT OF GIVING PROBIOTICS THROUGH DRINKING WATER ON INTERNAL ORGANS OF BALI DUCKS THAT GIVEN RATION CONTAINING GREEN BEANS SPROUTS PEELS - I M. D., Suwardisayoga; Siti, N. W.; Sukmawati, N. M. S. (Jurnal Peternakan Tropika, 2020)
This research aims to determine the influence of the administration of probiotics through drinking water on internal organs of bali ducks that given rations containing green bean sprouts peels.The research was carried out at the Sesetan Farm, Faculty of Animal Husbandry, Udayana University, on Jalan Raya Sesetan Gang Markisa no. 5 Sesetan, South Denpasar Sub-District for 8 weeks. The design used was a Completely Randomized Design (CRD) consisting of 3 treatments and 5 replications,so there were 15 experimental units.  Each unit used 3 female bali ducks with average body weight of 46.98 ± 7.18 g. The treatments were:the ducks that given drinking water without probiotics as a control (A), the ducks that given drinking water + 2.5 ml of probiotics (B), and the ducks that given drinking water + 5 ml of probiotics (C). The variableobserved was the percentage of heart, liver, provetriculus, ventriculus, bile, kidneys, small intestine and the long intestine. The results of this study showed that the percentage of internal organs of baliducks that given probiotics 2,5 ml and 5 ml in generallytended to be higher thanthe controls, but statistically notsignificantly different (P> 0.05).  Based on the results of the study, it can be concluded that the administration of probiotics through drinking water as much as 2.5 ml and 5 ml/tail/day on the Ducks that are given rations containing the skin of green beans sprouts no effect on the percentage of internal organs (percentage of heart, liver, proventriculus, ventriculus, bile, kidney, small intestine and long intestine) females bali duck aged of 8weeks. Key words: Bali ducks, internal organs, probiotics